The things we wish were true - Whalen, Marybeth (Seattle : Lake Union Publishing, 2016)
After an accident at the community pool and the return of a long-absent community member, the secret-filled lives of the residents of Sycamore Glen, North Carolina can no longer remain hidden from view.
Includes questions for discussion.
Keywords: Swimming pools -- Accidents -- Fiction; City and town life -- North Carolina -- Fiction; Interpersonal relations -- Fiction; Secrecy -- Fiction; North Carolina -- Fiction